Content Analysis and Coverage of News on Pandemic COVID-19 in Elected Newspapers (Indian Journal of Extension Education, 2022)
Newspapers have a significant impact on quality of life. Individuals are heavily influenced by the newspaper and it aids in promoting social awareness among them. This study was conducted to examine the content during pandemic COVID-19 in three selected newspapers viz., The Hindu, The Tribune and Punjab Kesari. A quantitative and qualitative analysis of the selected newspaper over the chosen time period was conducted during 2022. The majority of topics were covered in news format in all the newspapers. Newspaper correspondents were the primary information source in all the newspapers. The Hindu took up the most space and items. In all of the newspapers, the majority of the items and space were covered during PHASE-II.